COMPARATIVE STUDY OF PHYSICOMECHANICAL PROPERTIES OF ULTRABASIC ROCKS AND ANDESITES FROM CENTRAL MACEDONIA (GREECE) - Petrounias, P.; Rogkala, A.; Kalpogiannaki, M.; Tsikouras, B.; Hatzipanagiotou, K. (Bulletin of the Geological Society of Greece, 2016)
Petrographic, geochemical and physicomechanical features were determined and inter-correlated in two representative ultrabasic samples from the Veria-Naousa ophiolite and two Pliocenic andesite samples, occurring at the east of the above complex. Results show that mineralogical and textural features are major factors affecting the physicomechanical properties in both lithotypes. The ultrabasic rocks display higher resistance to attrition and abrasion and lower water absorption values relative to the intermediate volcanic rocks, hence the first are predicted to show better in-service engineering performance. However, the degree of serpentinisation is detrimental, as a highly serpentinised ultrabasic sample yielded poor results, analogous to the andesites, in certain laboratory tests. Ophiolite complexes in Greece are abundant and they are distributed along several mainland areas. Hence setting evaluation criteria for their quality is important as they can potentially replace limestones, which are less resistant and durable, in several environmental and industrial applications